Menurunkan Stres pada Penderita Hipertensi dengan Kombinasi Terapi Swedish Massage dan Aromaterapi Lavender: Reducing Stress in Hypertension Sufferers with a Combination of Swedish Massage Therapy and Lavender Aromatherapy - Billy Anoraga, Aditya; Nurwijayanti, Nurwijayanti; Prasetyo, Joko; Indasah, Indasah (Chakra Brahmanda Lentera Institute, 2024)
Severe stress is one of the main causes of hypertension in various age groups, ranging from the elderly, young adults, to middle age. Stress and high blood pressure are factors that cause hypertension. Hypertension that goes undetected and is not treated immediately can result in a variety of potentially fatal complications. This community service program aims to reduce stress in hypertensive patients in the community by providing a combination therapy of Swedish Massage and lavender aromatherapy. The method used is Pre post (pre experiment). This activity was held from April 28 to May 11, 2024 in the work area of the Karangan Health Center, Trenggalek Regency. The methods used were lectures, practices, and discussions involving 20 participants to measure stress reduction after being given the combination therapy. The way used to find out the reduction of stress in hypertensive patients in this program is through direct interviews using the Depression Anxiety Stress Scales sub-stress questionnaire instrument after receiving combination therapy. The results of the evaluation showed that participants understood hypertension, how to measure blood pressure, and how to do a combination therapy of Swedish Massage and lavender aromatherapy to reduce stress. In conclusion, Progressive Muscle Relaxation is effective in reducing stress in hypertensive patients.